2017
DOI: 10.6028/nist.ams.100-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of powder recycling on stainless steel powder and built material properties in metal powder bed fusion processes

Abstract: A series of 11 identical laser-based powder bed fusion (PBF) builds were completed with varying amounts of virgin and recycled nitrogen gas atomized S17-4 PH stainless steel powder following a specific powder recycling strategy that simulates industrial practice. Mechanical properties of parts were evaluated using tensile and hardness tests. Recycled powder properties, such as particle size distribution, flowability, chemical composition, and microstructure were evaluated. The recycled powder showed no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 16 publications
3
45
0
Order By: Relevance
“…The result of an even co-existence of both martensitic and austenitic phases in S17-4 produced in a nitrogen environment is consistent with the XRD results presented by Ref. [51]. Fig.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…The result of an even co-existence of both martensitic and austenitic phases in S17-4 produced in a nitrogen environment is consistent with the XRD results presented by Ref. [51]. Fig.…”
supporting
confidence: 81%
“…Reference [51] found that the amount of the FCC ɣ-austenite in their LPBF parts was approximately 95 %. This large percentage of austenite was attributed to the nitrogen gas atomization to produce the S17-4 powder, which leads to a higher content of nitrogen in the material, as found by Ref.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations